Overview Of The Readiness For The Implementation Of Electronic Medical Records For Outpatient Registration At Bumiayu Hospital Using The DOQ-IT Method - Fitriyani, Salsabila; Kusumawati, Nugraheni; Wibowo, Syifa Sofia; Belladiena, Alfiena Nisa (Health Science UDINUS, 2025)
The implementation of Electronic Medical Records (RME) at Bumiayu Hospital has not been evenly distributed. This is due to several factors, including the lack of special training for the registration sub-unit and the limited educational background of the officers who handle RME. In addition, the information technology infrastructure in hospitals is still not optimal, and governance and leadership support is considered inadequate. These conditions can affect the readiness of the system and reduce the accuracy in recording patient data. This study aims to describe the readiness of registration officers in the implementation of RME using the DOQ-IT method. The aspects studied include human resources, organizational culture, leadership governance, and IT infrastructure. The study uses a descriptive quantitative approach with a cross sectional approach. Data was collected using a questionnaire filled out by 4 registration officers. The results of the analysis on 4 variables show that hospitals are classified as very ready in the implementation of RME. The results of the study were dominated by women (75%) with Diploma education (75%) and a working period of >10 years (75%) The following are the readiness scores for the implementation of RME at Bumiayu Hospital: Human Resources (22.2), Organizational Work Culture (47.6), Leadership Governance (35.9), Information Technology Infrastructure (18.2). The Bumiayu Hospital Medical Record Installation should provide special training on the use of RME, especially for registration officers.